2013
DOI: 10.1103/physrevd.88.113002
|View full text |Cite
|
Sign up to set email alerts
|

Flavor-changing neutral currents in the minimal 3-3-1 model revisited

Abstract: We study a few ∆F = 2 and ∆F = 1 flavor changing neutral current processes in the minimal 3-3-1 model by considering, besides the neutral vector bosons Z ′ , the effects due to one CP -even and one CP -odd scalars. We find that there are processes in which the interference among all the neutral bosons is constructive or destructive, and in others the interference is negligible. We first obtain numerical values for all the unitary matrices that rotate the left-and right-handed quarks and give the correct mass o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 63 publications
0
67
0
Order By: Relevance
“…In [41] Further studies of the 331 model can be found in [407,408] where the lepton sector was analyzed in detail and in [409][410][411] where mixing of neutral mesons as well as a number of rare K and B d,s decays have been considered. The decay b → sγ was considered in [412,413] and in [414] also neutral scalar contributions were included.…”
Section: Modelmentioning
confidence: 99%
“…In [41] Further studies of the 331 model can be found in [407,408] where the lepton sector was analyzed in detail and in [409][410][411] where mixing of neutral mesons as well as a number of rare K and B d,s decays have been considered. The decay b → sγ was considered in [412,413] and in [414] also neutral scalar contributions were included.…”
Section: Modelmentioning
confidence: 99%
“…Store type was also a varying factor, with charities opposed to pedestrianisation as they required vehicular drop-offs, whilst cafés and restaurants were found to favour such a scheme. Retailers were shown to be mixed over whether to utilise a pedestrianised area and this would allow a free opportunity to strengthen the link between their environment, creating a living space to meet visitor needs (Gehl et al, 2006;Machado et al, 2013). If however they are unwilling to occupy the space and create this connection, the merit of such a scheme is diminished.…”
Section: Divide In Perceptions Of Retailersmentioning
confidence: 99%
“…Despite prioritising interventions for vacant stores (Figures 3 and 6) many retailers wished to pursue the default, even though they had stated it not to be working. The divide in retailers wishing to attend trader association meetings is also a concern as it has been reported that improved communication among stakeholders allows a retail area to better respond to visitors (Machado et al, 2013;Medway et al, 2000). Difficulty in attending meetings can be understood due to limitation for SMEs with previous research showing that many traders find it difficult to collaborate with each other due to financial and time constraints (Hall, 2015;LSE Cities, 2017) however the finding that 40% would never attend regardless of incentives is troubling as Hall (2015) states, business associations are places where retailers are able to engage in change.…”
Section: Divide In Perceptions Of Retailersmentioning
confidence: 99%
“…(9) and (10) give the correct quark masses (at the Z-pole given in Ref. [20]) and the CKM All these couplings should be multiplied by √ 2, it is a conversion factor from the notation used in [20] to our notation.…”
Section: B Quarksmentioning
confidence: 99%
“…On the equations above we have considered the V U L,R and V D L,R matrices to be real, that is because we considered the numerical results presented in [20] for such matrices and for the Yukawa couplings [see Eqs. (9) and (10)].…”
Section: The Neutron Edmmentioning
confidence: 99%